Chaplin, the collection - Chaplin, Charles (Madacy Music Group [distribución])
Este volumen incluye los cortometrajes: His new job (1920), The champion (1916), producidos por The Essanay Films Manufacturing Company, y Face on the bar room floor (Keystone, 1920).